Profile of subjective quality of life and its correlates in a nation-wide sample of high school students in an Arab setting using the WHOQOL-Bref - Al-Fayez, Ghenaim A (BioMed Central, 2011)
BACKGROUND: The upsurge of interest in the quality of life (QOL) of children is in line with the 1989 Convention on the Rights of the Child, which stressed the child's right to adequate circumstances for physical, mental, and social development. The study's objectives were to: (i) highlight how satisfied Kuwaiti high school students were with life circumstances as in the WHOQOL-Bref; (ii) assess the prevalence of at risk status for impaired QOL and establish the QOL domain normative values; and (iii) examine the relationship of QOL with personal, parental, and socio-environmental factors. METHOD: A nation-wide sample of students in senior classes in government high schools (N = 4467, 48.6% boys; aged 14-23 years) completed questionnaires that included the WHOQOL-Bref. RESULTS: Using Cummins' norm of 70% - 80%, we found that, as a group, they barely achieved the well-being threshold score for physical health (70%), social relations (72.8%), environment (70.8%) and general facet (70.2%), but not for psychological health (61.9%). These scores were lower than those reported from other countries. Using the recommended cut-off of <1SD of population mean, the prevalence of at risk status for impaired QOL was 12.9% - 18.8% (population age-adjusted: 15.9% - 21.1%). In all domains, boys had significantly higher QOL than girls, mediated by anxiety/depression; while the younger ones had significantly higher QOL (p < 0.001), mediated by difficulty with studies and social relations. Although poorer QOL was significantly associated with parental divorce and father's low socio-economic status, the most important predictors of poorer QOL were perception of poor emotional relationship between the parents, poor self-esteem and difficulty with studies. CONCLUSION: Poorer QOL seemed to reflect a circumstance of social disadvantage and poor psychosocial well-being in which girls fared worse than boys. The findings indicate that programs that address parental harmony and school programs that promote study-friendly atmospheres could help to improve psychosocial well-being. The application of QOL as a school population health measure may facilitate risk assessment and the tracking of health status.